Applying Linguistic Analysis in the Investigation of Crimes against Sexual Inviolability and Sexual Freedom of the Individual - E. A. Pashina (Теория и практика судебной экспертизы)
The paper is devoted to understanding the provisions of the Penal Code of the Russian Federation concerning crimes against sexual inviolability and sexual freedom of the individual. The potential for using special knowledge of linguistics in the criminal investigation of such offenses is explored based on the analysis of the wording of relevant articles in the Code, determining the purpose of communication, characterizing interaction between communicating parties, and establishing the scope of linguistic expert competence.